A Recalculation of the Dissociation Constant of AlSO4+ and the Corresponding Thermodynamic Functions - Mahaseth, Awadhesh; Jha, S.N.; Jha, S.K. (Asian Journal of Chemistry, 2010)
We have measured the dissociation constant of AlSO4+ ⇄ Al3+ + SO42– at 5º, 15º, 25º and 35ºC from Sharma and Prasad's values of EMF of Cell-C1 and other data using improved equations and modifying the method of computation of results. Our results are entirely different from those reported by Sharma and Prasad.